The Western intellectual tradition : from Leonardo to Hegel - Bronowski, Jacob, 1908-1974 (Harper, 1960)
This is intellectual history in the largest sense, not confined to ideas in one or a few fields, but covering the whole spectrum of Western intellectual activity during the four centuries when the world was transformed from medieval to modern. An important feature of the book is its stress on the interplay of ideas from different fields. In particular, the authors give more attention than is usual to the ideas of science, to the movements of literary style, and to the innovations in the arts. This is a profound and evocative history of the life of ideas in their full setting: of men, of groups of men, of events.